The dihydropyridine receptor: expression of 190 kD alpha 1 subunit in crayfish muscle - Hudecová, S; Krizanová, O (General physiology and biophysics, 1991)
The existence of dihydropyridine receptor in crayfish striated muscle was proved by Northern blot analysis and 3H PN 200--110 binding. The alpha 1 subunit is encoded by a 8300 nt mRNA population and is expressed as 190 kD protein in crayfish T-tubular system, which binds 3H PN 200--110 (Bmax 1.5 +/- 0.4 pmol/mg protein and KD 6.2 +/- 0.8 nmol/l). The purified protein is phosphorylated by cAMP-dependent protein kinase. The dihydropyridine receptor in crayfish striated muscle also contains alpha 2 subunit, which on Northern blot gives the same signal as the alpha 2 subunit from rabbit skeletal muscle.
Keywords: Molecular Weight; messenger RNA; Calcium Channel Blockers; molekulová hmotnost; Calcium Channels; Muscles; blokátory kalciových kanálů; Protein Conformation; Astacoidea; Gene Expression; nikotinové receptory; zvířata; RNA, Messenger; svaly; severní raci; Receptors, Nicotinic; exprese genu; vápníkové kanály; konformace proteinů; Animals